PENGARUH KOMPLEKSITAS PERATURAN PERPAJAKAN, KUALITAS LAYANAN, SANKSI PERPAJAKAN DAN PEMERIKSAAN TERHADAP KEPATUHAN PAJAK - Wiyarni, Wiyarni; Hartini, Hartini; Djuharni, Darti (Widya Mandala Surabaya Catholic University, 2018)
Improving taxpayer compliance is a very important key in order to increase state revenues from the tax sector. This study aims to examine the variables of the com-plexity of tax regulations, service quality, taxation sanctions and tax audit on indi-vidual taxpayer compliance at the Singosari Pratama Tax Service Office. This research is a quantitative research with hypothesis testing which will be analyzed using multiple linear regressions. The population in this study is an individual taxpayer who earns income from a free business registered at KPP Pratama Singosari ammounted 11,500 taxpayers. By using probability sampling as a sampling technique, the number of respondents from this study was 100 people. The results of this study state that the complexity of tax regulations, service quality, tax sanctions and tax audits have a significant effect on tax compliance. The amount of the variable contribution to the complexity of tax regulations, service quality, tax sanctions and examination of tax compliance is 97.2%. Partial testing results also indicate that the variable complexity of tax regulations, taxation sanctions and tax audits have a significant effect on individual taxpayer compliance. The results of this study indicate that partially service quality variables do not significantly influence individual taxpayer compliance.